2019
DOI: 10.1186/s13073-019-0697-8
|View full text |Cite
|
Sign up to set email alerts
|

Neoantigen-specific immunity in low mutation burden colorectal cancers of the consensus molecular subtype 4

Abstract: BackgroundThe efficacy of checkpoint blockade immunotherapies in colorectal cancer is currently restricted to a minority of patients diagnosed with mismatch repair-deficient tumors having high mutation burden. However, this observation does not exclude the existence of neoantigen-specific T cells in colorectal cancers with low mutation burden and the exploitation of their anti-cancer potential for immunotherapy. Therefore, we investigated whether autologous neoantigen-specific T cell responses could also be ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…7b ) within the DP TIL fraction in HPV− patients are most likely tumor antigen-specific, but were not detected as such using our mutated short peptide/MHC I binding algorithm approach. In collaboration with a group in the Netherlands, we showed that in colon cancer patients, reactivity to neoantigens was confined to the CD103+ CD39+ CD8+ TIL 45 . Recent studies have highlighted limitations in current mutated antigen pipelines suggesting that intronic regions could contribute to the neoantigen pool 46 and some of the T-cell responses could be directed to overexpressed self-antigens.…”
Section: Discussionmentioning
confidence: 94%
“…7b ) within the DP TIL fraction in HPV− patients are most likely tumor antigen-specific, but were not detected as such using our mutated short peptide/MHC I binding algorithm approach. In collaboration with a group in the Netherlands, we showed that in colon cancer patients, reactivity to neoantigens was confined to the CD103+ CD39+ CD8+ TIL 45 . Recent studies have highlighted limitations in current mutated antigen pipelines suggesting that intronic regions could contribute to the neoantigen pool 46 and some of the T-cell responses could be directed to overexpressed self-antigens.…”
Section: Discussionmentioning
confidence: 94%
“…This subtype is also associated with worst clinical prognosis [119,121,122]. Patients diagnosed with CMS4 colorectal cancers were shown to carry neoantigen-reactive T cells despite the fact that these patients do not benefit from checkpoint blockade in an advanced setting [123,124]. In addition, these tumours display some hallmarks of ongoing anti-tumour immunity and inflammatory processes, indicating a certain degree of immunogenicity that might be counterbalanced by TGF-β [123].…”
Section: Combined Targeting Of Tgf-β and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Patients diagnosed with CMS4 colorectal cancers were shown to carry neoantigen-reactive T cells despite the fact that these patients do not benefit from checkpoint blockade in an advanced setting [123,124]. In addition, these tumours display some hallmarks of ongoing anti-tumour immunity and inflammatory processes, indicating a certain degree of immunogenicity that might be counterbalanced by TGF-β [123]. In mice models that recapitulate the CMS4 molecular subtype, exclusion of CD4 + and CD8 + T cells could be explained by the presence of high Tgf-β levels that were produced by CAFs and other cells of the TME.…”
Section: Combined Targeting Of Tgf-β and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Viral HNSCC display only half of the mutations rate observed in non-viral HNSCC (125,126). CD8+ T cells responding to such mutations have been detected in a few patients with non-OPSCC either spontaneously induced (127) or following a complete response after pembrolizumab treatment (128). Notably, such neoantigen specific T cells can also be detected in low TMB tumors (129), suggesting that they may also be present in OPSCC.…”
Section: The Role Of Tumor-specific T Cells In the Tme Of Opsccmentioning
confidence: 99%